The Implementation of Scavenger Hunt Game in Teaching Reading Comprehension of Descriptive Text - Anggre Oktarind (The Study Program of English Education of Palangka Raya University, 2022)
One of the English skills, namely reading, should be mastered by students so they can understand and comprehend the text they read. However, many students have lack of ability in reading especially in reading descriptive text. This research was aimed to find the effectiveness of implementing Scavenger Hunt game in teaching reading comprehension of descriptive text. This research used the one group of pre-test and post-test design without control group with the research sample is tenth graders of SMA Negeri 1 Palangka Raya in the academic year 2021/2022 with the number of sample was 39 students. The data were obtained by using pre-test and post-test in multiple choice test items in relation to descriptive texts to measure the students’ reading comprehension. The data were analysed using Wilcoxon Signed Rank test since the data was not normally distributed. The result showed that there was significant effect of implementing Scavenger Hunt game (p<0.01) in teaching reading of descriptive text at the secondary school.